2020
DOI: 10.1590/1676-0611-bn-2019-0897
|View full text |Cite
|
Sign up to set email alerts
|

Twigs occupied by Pheidole Westwood, 1839: Is there a difference between species?

Abstract: Pheidole is a genus with wide geographical distribution and diversity, especially in the leaf litter of neotropical forests, where nests are found at the soil-litter interface, in the soil and vegetation, among leaves, seeds, and twigs. Despite the availability of twigs and Pheidole species diversity in the leaf litter, most of this resource is not occupied, which suggests the existence of filters. This study analyzes whether twigs occupied by Pheidole species differ for the outer structure and anatomy of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…However, there was not enough data to test for differences in ant traits according to substrate features. Barroso et al (2020), in Brazil, found that different species of Pheidole colonized twigs with different wood anatomy and structure, which suggests that wood structure determines preference for twig occupation. Test 1 Figure 3.…”
Section: Test 1: Substrate Comparison (Cc Vs Ct)mentioning
confidence: 99%
“…However, there was not enough data to test for differences in ant traits according to substrate features. Barroso et al (2020), in Brazil, found that different species of Pheidole colonized twigs with different wood anatomy and structure, which suggests that wood structure determines preference for twig occupation. Test 1 Figure 3.…”
Section: Test 1: Substrate Comparison (Cc Vs Ct)mentioning
confidence: 99%
“…In the leaf litter, Pheidole may occupy fruits, seeds, and wood in varying degrees of decomposition (Castaño-Menzes et al 2015;Casadei-Ferreira 2021), and the latter includes twigs (Fernandes et al 2019). Barroso et al (2020) and Almeida et al (2021) suggested that the occupation of twigs by species of Pheidole could be due to a process of selection. Pheidole tijucana Borgmeier, 1927 belongs to the (Feitosa et al 2021;Silva et al 2022).…”
Section: Introductionmentioning
confidence: 99%